2022
DOI: 10.1038/s41467-022-35289-z
|View full text |Cite
|
Sign up to set email alerts
|

Colossal Nernst power factor in topological semimetal NbSb2

Abstract: Today solid-state cooling technologies below liquid nitrogen boiling temperature (77 K), crucial to quantum information technology and probing quantum state of matter, are greatly limited due to the lack of good thermoelectric and/or thermomagnetic materials. Here, we report the discovery of colossal Nernst power factor of 3800 × 10−4 W m−1 K−2 under 5 T at 25 K and high Nernst figure-of-merit of 71 × 10−4 K−1 under 5 T at 20 K in topological semimetal NbSb2 single crystals. The observed high thermomagnetic pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 60 publications
(91 reference statements)
5
15
0
Order By: Relevance
“…Above 100 K, the S xx decreases linearly with increasing temperature, reaching À20 mV K À1 at 300 K. When the magnetic field is applied, the S xx below 100 K is significantly enhanced, while that above 100 K is only slightly increased. Similar temperature-dependence and magnetic field-dependence have been also observed in single-crystalline NbSb 2 , 20 indicating that the grain boundary has little influence on the S xx .…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…Above 100 K, the S xx decreases linearly with increasing temperature, reaching À20 mV K À1 at 300 K. When the magnetic field is applied, the S xx below 100 K is significantly enhanced, while that above 100 K is only slightly increased. Similar temperature-dependence and magnetic field-dependence have been also observed in single-crystalline NbSb 2 , 20 indicating that the grain boundary has little influence on the S xx .…”
Section: Resultssupporting
confidence: 72%
“…For example, the S yx of polycrystalline NbSb 2 is 396 mV K À1 under 9 T at 21 K, which is 36% lower than that of single-crystalline NbSb 2 (616 mV K À1 ) under the same conditions. 20 Thus, the grain boundaries in polycrystalline NbSb 2 lead to decreased S yx .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, we attribute both the giant electron mobility and the enhanced thermoelectric performance in Mn-doped Mg 3+d Bi 2 to the topological phase transition from a Z 2 topological insulator to a Dirac semimetal. We calculated the transverse zT value for the obtained Mg 3+d Bi 2 :Mn 0.1 sample at 6 Tesla and the best zT is 0.025 at 15 K, which is comparable with the state-of-the-art transverse thermoelectric materials, such as single-crystal NbSb 2 (zT = 0.1, at 25 K), 42 PtSn 4 (zT = 0.01, at 15 K), 11 Mg 2 Pb (zT = 0.01, at 25 K), 21 YbMnBi 2 (zT = 0.002, at 175 K), 6 etc. (Fig.…”
Section: Topological Phase Transition Induced By Mn Dopingsupporting
confidence: 57%
“…Finally, transverse thermoelectric materials have great potential in thermoelectric energy conversion, especially in Recently, researchers suggested that the specific heat pumping powers of transverse thermoelectric materials are higher than those of liquid hydrogen and liquid nitrogen. 21,42 Additionally, compared with longitudinal thermoelectric devices, the transverse thermoelectric devices do not need both n and p types of thermoelectric materials for constructing one device, which significantly simplifies the thermoelectric module. The main problem in the future is that transverse thermoelectric materials still need a high magnetic field to achieve high performance.…”
Section: Papermentioning
confidence: 99%